PERAN FILANTROPI DI MASYARAKAT (Studi Analisis terhadap konsep dalam Sistem Ekonomi Sosialisme dan Sistem Ekonomi Syariah) - Chonita Lutfyah; Pamela Vernanda; Annisa Amalia Wati; Devi Rahmadhiyanti; Natasya Samantha; Ani Faujiah (STAI AN-NAJAH INDONESIA MANDIRI, 2021)
The main purpose of this research is to find out how philanthropy is in the concept of socialist economic system and sharia economic system. This study uses a qualitative descriptive research method with a literature analysis study (library research). There are advantages and disadvantages to this philanthropy for the state. Islamic philanthropy is a term that emerged in modern times as a result of the adoption of the word. This kind of philanthropy activity has taken place before the existence of Islam because the discourse of social justice has developed from before the existence of Islam. In Indonesian, a term that is quite similar to philanthropy is social generosity, which includes zakat, infaq, alms, and waqf (ZISWAF).In theory, the concept of philanthropy as a mechanism for distributing wealth is the activity of diverting a portion of wealth or material assets from those who have a capable economy, to be distributed to those who are less fortunate in their economy. This proves that zakat, infaq, alms, and waqf, or philanthropic institutions are public or social institutions that play a major role in the socio-economic community. Islamic philanthropy (zakat, infaq, alms, and waqf) is a solution to people's problems and humanitarian problems, especially poverty. So the poverty alleviation effort is to develop and manage ZISWAF funds optimally, or by managing funds productively. Through the CSR (Corporate Social Responsibility) program, business actors are not only concerned with profit but also contribute to society such as PT Sido Muncul. Keywords : Philanthropy, Socialist Economic System, Sharia Economic System References Abdiyansyah linge.